Neural circuits underlying thirst and fluid homeostasis - Zimmerman, Christopher A. (Nat Rev Neurosci, 2017)
Thirst motivates animals to find and consume water. More than forty years ago, a set of interconnected brain structures known as the lamina terminalis (LT) was identified that governs thirst. However, due to the anatomical complexity of these brain regions, the structure and dynamics of their underlying neural circuitry has remained obscure. Recently, the emergence of new tools for neural recording and manipulation has reinvigorated the study of this circuit and prompted reexamination of longstanding questions about the neural origins of thirst. Here we review these advances, discuss what they teach us about the control of drinking behavior, and outline the key questions that remain unanswered.